A maternal Western diet during gestation and lactation modifies offspring's microglial cell density and morphology in the hippocampus and prefrontal cortex in Yucatan minipigs. (20th November 2020) - Val-Laillet, David; Kanzari, Ameni; Guérin, Sylvie; Randuineau, Gwénaëlle; Coquery, Nicolas
Highlights: Western diet during pregnancy and lactation increases microglial cell density in the prefrontal cortex of offspring. Western diet during pregnancy and lactation predisposes offspring to changes in microglial cells morphology. Changes in microglial cells were different between the hippocampus and prefrontal cortex. Abstract: Changes in microglial development and morphology can be induced by inflammatory conditions and associated with eating or mood disorders, such as hyperphagia or depression. In a previous paper in the minipig model, we showed that maternal Western diet during gestation and lactation decreased hippocampus neurogenesis and food-rewarded cognitive abilities in the progeny. Whether these alterations are concomitant with a central inflammatory process in brain structures involved in learning and memory (hippocampus, HPC), cognitive (prefrontal cortex, PFC), or hedonic (orbitofrontal cortex, OFC) control of food intake is still unknown. In the present study, Yucatan minipigs ( Sus scrofa ) sows were exposed to two different diets during gestation and lactation (standard, SD N = 7 vs . Western diet, WD N = 9). Iba1 is a calcium-binding protein specifically expressed in microglia in the brain, which plays an important role in the regulation of the microglia function. Iba1 expression was examined by immunohistochemical analyses in the PFC, OFC and HPC of piglets. The density of microglial cells, as well as their morphology, were assessed in order to have an indirect insight of microglial cell activation state possibly in relationship with neuroinflammation. The density of Iba1-positive cells was higher in the PFC but not in the HPC of WD compared to SD piglets ( p < 0.001). In the HPC, anterior and dorsolateral PFC, WD piglets had more unipolar cells, contrary to SD that had more multipolar cells ( P < 0.0001). Opposite effects were observed in the OFC, with SD presenting more unipolar ( P < 0.001) microglial cells compared to WD. We showed here that maternal diet during pregnancy and lactation had significant effects on morphological changes of microglial cells in the offspring, and that these effects differed between the HPC and PFC, suggesting different response mechanisms to the early nutritional environment.